2014
DOI: 10.1161/strokeaha.114.005648
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality After First-Ever and Recurrent Stroke in Young Adults

Abstract: Background and Purpose-Mortality after first-ever stroke, and particularly after recurrent stroke, and predictors of longterm mortality among young and middle-aged stroke patients are not well-known. We assessed 17-year risk of mortality with focus on the effect of recurrence on the risk of death of young and middle-aged patients with stroke. Methods-Mortality and recurrent stroke rate of 970 consecutive 30-day survivors of first-ever ischemic stroke aged 15 to 49 years (1994)(1995)(1996)(1997)(1998)(1999)(200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
5
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 35 publications
6
93
5
4
Order By: Relevance
“…Similar to a previous study from our group, 2 they observed an increased long-term mortality compared with the general population, expressed as the standardized mortality ratio (SMR). Aarnio et al 1 commented that the SMR observed in their study was remarkably 2× higher than in ours and that the reasons for this difference are unclear. In the following, we try to clarify this difference.…”
Section: To the Editorcontrasting
confidence: 69%
“…Similar to a previous study from our group, 2 they observed an increased long-term mortality compared with the general population, expressed as the standardized mortality ratio (SMR). Aarnio et al 1 commented that the SMR observed in their study was remarkably 2× higher than in ours and that the reasons for this difference are unclear. In the following, we try to clarify this difference.…”
Section: To the Editorcontrasting
confidence: 69%
“…Stroke is a frequently occurring disease among the elderly, although there has been a clear increase in the incidence rate of stroke in young and middle-aged patients (14). The rate of stroke-induced disabilities can reach as high as 80% (15).…”
Section: Discussionmentioning
confidence: 99%
“…Conterno LO et al -Gravidade do déficit neurológico ... orgânica causada por múltiplas agressões, a síndrome de imobilidade e perda de independência e a desnutrição decorrente desse estado [31].…”
Section: Artigo Originalunclassified
“…Comparando a evolução dos pacientes, observamos que aqueles que desenvolveram IH tiveram taxas mais elevadas de óbito quando comparadas com pacientes sem IH. Diversos estudos têm demonstrado este mesmo impacto negativo das infecções na evolução dos pacientes com AVC [25,29,31].…”
Section: Artigo Originalunclassified